Scenario Planning for Esg Implementation at PT Kereta Api Indonesia (Persero) - Jehan Nurbani; Santi Novani (Departement of Mathematics Education, 2023)
Sustainable business is currently become an important issue, because it can give added value beside the economic value, that is beneficial for environmental, social, and governance. Therefore, ESG (Environmental, Social, and Governance) concept is implemented to achieve this target. PT Kereta Api Indonesia (Persero) currently have a plan for ESG implementation, that is also having a challenge in the process. The objective of this study is to analyze the possible scenarios for ESG implementation. This study used qualitative method, where the data is obtained with primary data and secondary data. Data obtained is analyzed using tools such as PESTEL, Porter's Five Forces, and Resource-Based View. Then, it was continued with scenario planning analysis, using 5 stages, including 1) orientation, 2) exploration, 3) scenario creation, 4) option creation, and 5) integration. The study resulted 4 scenarios, 1) High-speed Railway, 2) Commuter Line, 3) Steam Locomotive, and 4) Diesel Locomotive. These scenarios were created by considering the two critical uncertainties from identified driving forces which are government’s regulation and funding policy. Through these four scenarios generated, the company is expected to be able to deal with uncertainties in the future well, so that ESG implementation plan can run effectively and efficiently.